Legal Analysis on The Role from Financial Services Authority in The Field from Legal Protection for Costumers and Supervision from Banks - Prasasti Dyah Nugraheni (Law Research Review Quarterly, 2025)
Financial Services Authority is an institution that is free of interference of other institutions and is independent. This Financial Services Authority has various functions, various powers, and various tasks in the field from examination, regulation, supervision, and investigation from all financial institutions in Indonesia. One type of financial institution is a bank financial institution. The various functions, powers, and duties from Financial Services Authority have been regulated and stipulated in Law Number 21 from the Year 2011 about Financial Services Authority. Besides, Financial Services Authority also has various functions, various powers, and various tasks in the field from legal protection for all customers owned by all banks in Indonesia. This is done to provide legal certainty and legal protection guarantees for all customers owned by all banks in Indonesia. In writing the scientific article, the writer uses a normative and juridical research method that means a research method that is carried out using various sources of library law or secondary sources of law to find various solutions to various existing legal problems